2013
DOI: 10.1021/tx400215z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolites of Di-2-ethylhexyl Adipate (DEHA) as Biomarkers of Exposure in Human Biomonitoring Applications

Abstract: Di-2-ethylhexyl adipate (DEHA) is a common plasticizer used in food packaging. At high doses, DEHA can cause adverse health effects in rats. Although the potential for human exposure to DEHA is high, no DEHA specific biomarkers are identified for human biomonitoring. Using human liver microsomes, we investigated the in vitro phase I metabolism of DEHA and its hydrolytic metabolite mono-2-ethylhexyl adipate (MEHA) and, for comparison purposes, of the analogous di-2-ethylhexyl phthalate (DEHP) and its hydrolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…However, human metabolites of DEHTP are unknown. In vitro studies have been used to identify metabolites of xenobiotic chemicals (Moslemi et al, 1993; Muhitch, 1993; Treadway and Pelkonen, 2006; Zulalian et al, 1993) which can be used as biomarkers of exposure to these chemicals (Silva et al, 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…However, human metabolites of DEHTP are unknown. In vitro studies have been used to identify metabolites of xenobiotic chemicals (Moslemi et al, 1993; Muhitch, 1993; Treadway and Pelkonen, 2006; Zulalian et al, 1993) which can be used as biomarkers of exposure to these chemicals (Silva et al, 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…Two additional oxidative metabolites were identified in in vitro studies and proposed, in addition to MEHA, as specific human biomarkers of exposure to DEHA. However, their excretion rates seem to be low and the preliminary results suggested that their application may be limited to the highly exposed populations [ 76 ]. Indeed, a very recent pharmacokinetic study reported mean urinary excretion rates of three oxidized metabolites in humans between 0.05 % and 0.20 % [ 33 ].…”
Section: Identification Of Potential Wbe Biomarkers Of Human Exposurementioning
confidence: 99%
“… Compound Biomarker Excretion rate (%) a Ref. Di-2-ethylhexyl adipate (DEHA) Mono-2-ethylhexyl adipate (MEHA) NA [ 76 ] b Mono-5-carboxy-2-ethylpentyl adipate (5cx-MEPA) 0.20 (0.17–0.24) [ 33 ] c Mono-2-ethylhydroxyhexyl adipate (5OH-MEHA) 0.07 (0.03–0.10) Mono-(2-ethyl-5-oxohexyl) adipate (5oxo-MEHA) 0.05 (0.01–0.06) Di(2-ethylhexyl) terephthalate (DEHTP) 1-Mono-(2-ethyl-5-carboxyl-pentyl) terephtahalate (5cx-MEPTP) 13.0 (7.0–20.4) [ 79 ] d 1-Mono-(2-ethyl-5-hydroxy-hexyl) terephtahalate (5OH-MEHTP) 1.8 (1.3–2.4) 1-Mono-(2-ethyl-5-oxo-hexyl) terephtahalate (5oxo-MEHTP) 1.0 (0.57–1.6) 1-Mono-(2-carboxyl-methyl-hexyl) terephtahalate (2cx-MEHTP) 0.28 (0.17–0.42) Di(isononyl)cyclohexane-1,2-dicarboxylate (DINCH) Cyclohexane-1,2-dicarboxylate-mono-(7-hydroxy-4-methyl) octyl ester (OH-MINCH) 10.7 (7.7–12.9) [ 81 ] d 14.5 (9.2–17.6) [ 82 ] e Cyclohexane-1,2-dicarboxylic mono oxoisononyl ester (oxo-MINCH) 2.0 (1.5–2.6) [ 81 ] d 4.8 (2.9−7.5) [ 82 ] e Cyclohexane-1,2-diarboxylic mono carboxyisononyl ester (cx-MINCH) 2.0 (1.8–2.3) [ 81 ] ...…”
Section: Identification Of Potential Wbe Biomarkers Of Human Exposurementioning
confidence: 99%
“…Other potential plasticizers detected were 2,3-bis-(2-hydroxyethyl)glucitol and MEOHA (mono-2-ethyloxoexyl adipate). It is worth noting that MEOHA can be considered a proper NIAS, as it was found to be an oxidative metabolite of DEHA (2-ethylexyl adipate), which is widely used as a plasticizer for food contact plastics [49].…”
Section: Identification Of Nias Present In a Starch-based Biopolymermentioning
confidence: 99%